ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN ANGGARAN BELANJA DENGAN PERENCANAAN ANGGARAN SEBAGAI PEMODERASI PADA PEMERINTAH KOTA DEPOK TAHUN 2013-2017. - Ani, Lelly; Mulyadi, JMV; Pratowo, Dwi (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2020)
Lelly Ani1, JMV. Mulyadi2, Dwi Pratowo3 Pemerintah Kota Depok1,Sekolah Pascasarjana Universitas Pancasila23 lellyani79@gmail.com Abstract The research objective was to analyze factors influencing the budget absorption in Depok Municipality with Budget Planning as a moderating variable. The research was causal associative research. It applied survey research methodology. The population was 190 respondents that consisted of the users of budget/authority to use budget, commitment makers, financial administrative officials, activity technical executors, and treasurer for expenditures in 38 SKPDs. The data were gathered by using questionnaires SKPD in Depok Municipality. The total sample of respondents was 114 peoples. The data were processed using multiple regression and residual analysis. The results showed that Human Resources Competence, the process of procurement of goods and services, and organizational commitment partially have a significant positive effect on the absorption of Depok City budget. Budget planning which is a moderating variable can strengthen the relationship between Human Resources Competence towards budget absorption, but budget planning does not strengthen the relationship between the procurement of goods and services, and organizational commitment to the absorption of the Depok City budget.